2021
DOI: 10.3390/ma14030678
|View full text |Cite
|
Sign up to set email alerts
|

Copper–Calcium Hydroxide and Permanent Electrophoretic Current for Treatment of Apical Periodontitis

Abstract: Endodontic failure has been and continues to be a problem for endodontics-specialists. Complicated anatomy, numerous foramens, and accessory canals are an environment for microorganisms to infect the teeth. The purpose of the present work was to evaluate the regeneration of copper–calcium hydroxide (Cupral)-endodontically treated teeth diagnosed with apical periodontitis using an electrophoresis technique. In total, 132 patients, aging from 19 to 65 years old, underwent endodontic treatment mono- and multi-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The study conducted by Meto et al [ 34 ], which was removed from this systematic review due to its case report design, tested the efficacy of Cupral ® , a copper-calcium hydroxide solution, as a disinfectant on a biofilm-contaminated aligner. This is an innovative method; its effectiveness has been demonstrated in periodontal or endodontic infections [ 35 , 36 ], but never in orthodontics, and its mechanisms of action remain unknown. In this study, Cupral ® showed encouraging results in terms of elimination of aerobic and anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Meto et al [ 34 ], which was removed from this systematic review due to its case report design, tested the efficacy of Cupral ® , a copper-calcium hydroxide solution, as a disinfectant on a biofilm-contaminated aligner. This is an innovative method; its effectiveness has been demonstrated in periodontal or endodontic infections [ 35 , 36 ], but never in orthodontics, and its mechanisms of action remain unknown. In this study, Cupral ® showed encouraging results in terms of elimination of aerobic and anaerobic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Another study used copper-calcium hydroxide nanoparticles for treating apical periodontitis in an endodontically treated tooth, and it recommended using them to treat periodontitis [ 102 ]. Researchers have used several copper nanoparticle formulations for periodontal therapy.…”
Section: Copper Nanoparticles In Dental Materialsmentioning
confidence: 99%
“…Caries, dental trauma and tooth malformations frequently cause an infection of the dental pulp, which results, if untreated, in pulpitis, pulp necrosis and, finally, apical periodontitis. In this case, root canal treatment (RCT) is indicated, as the removal of necrotic pulp tissue and bacteria from the entire canal system enables healing of periapical pathosis [1][2][3]. During RCT, the endodontic canal system has to be explored, and the canals are enlarged and debrided by endodontic files.…”
Section: Introductionmentioning
confidence: 99%